Cerebrospinal Fluid Profile in Suspected Leptomeningeal Metastases in Dr. Cipto Mangunkusumo National Referral Hospital and Dharmais National Cancer Center Hospital - Aninditha, Tiara; Maulina, Lisa; Andriani, Rini; Susanto, Eka; Ranakusuma, Teguh; Sofyan, Henry Riyanto (Indonesian Journal of Cancer, 2025)
Background: Leptomeningeal metastases (LM) are a condition in which malignant cells spread to the leptomeninges and subarachnoid space, with an increasing incidence and poor prognosis. Cerebrospinal fluid (CSF) analysis is an important examination, with cytology as the gold standard for detecting malignant cells in CSF. We aim to describe the CSF profile (i.e. protein, glucose, cell count, and cytology) in detecting malignant cells among patients with suspected LM in Cipto Mangunkusumo National Referral Hospital and Dharmais National Cancer Center Hospital from January 2018 to December 2021. Method: A multicenter cross-sectional retrospective study was conducted to describe the CSF profile in suspected LM from January 2018 to December 2021. Suspected LM cases were established from clinical and radiological findings. The lumbal puncture was performed in those suspected LM cases. Clinical manifestations, radiological data, tumor type, some aspects from CSF routine analysis (i.e. protein, glucose, cell count), and lumbar puncture frequency were described. Their correlation with CSF cytology was analyzed. Results: There were 153 subjects with abnormalities on CSF routine analysis (75.2%), consisting of CSF cell count 5/uL (47.1%) with a median of 5 (1–3504)/uL, CSF protein 45 mg/dL (52.9%) with a median of 50 (5–820) mg/dL, and CSF glucose 50 mg/dL (15%) with a median of 68 (3–629) mg/dL. The positive CSF cytology result was 20.3%. Positive CSF flow cytometry immunophenotyping in hematological malignancy with suspected LM was 25.6%. There was a significant correlation between the increase in CSF cell count, hematological malignancy, and MRI results with CSF cytology (p 0.001; p = 0.03; p = 0.03). There was no significant correlation between clinical manifestations and lumbar puncture frequency with CSF cytology.Conclusion: Abnormalities in CSF routine analysis were found in the majority of subjects with suspected LM, but the CSF cytology positivity rate was considered low. The presence of varied clinical symptoms and repeated lumbar punctures didn’t increase the likelihood of positive CSF cytology